2005
DOI: 10.1021/pr049820r
|View full text |Cite
|
Sign up to set email alerts
|

Genistein Reverses Changes of the Proteome Induced by Oxidized-LDL in EA·hy 926 Human Endothelial Cells

Abstract: Endothelial cells are primary targets for pro-atherosclerotic stressors such as oxidized LDL (ox-LDL). The isoflavone genistein, on the other hand, is suggested to prevent a variety of processes underlying atherosclerosis and cardiovascular diseases. By analyzing the proteome of EA.hy 926 endothelial cells, here we show, that genistein reverses the ox-LDL-induced changes of the steady-state levels of several proteins involved in atherosclerosis. These alterations caused by genistein are functionally linked to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 49 publications
(87 reference statements)
0
22
0
Order By: Relevance
“…Due to its potential cardioprotective role and favorable safety profile, genistein has received substantial attention over the last few years. It has been revealed that genistein not only affects the expression of atherosclerosis-relevant genes but also inhibits lesion and thrombus formations caused by endothelial stressors such as oxidized LDL or homocysteine [27][28][29][30] . In addition, genistein is effective in ameliorating cardiovascular profiles in experimental models of postmenopausal metabolic syndrome 31 .…”
Section: Evidence From the Women's Healthmentioning
confidence: 99%
“…Due to its potential cardioprotective role and favorable safety profile, genistein has received substantial attention over the last few years. It has been revealed that genistein not only affects the expression of atherosclerosis-relevant genes but also inhibits lesion and thrombus formations caused by endothelial stressors such as oxidized LDL or homocysteine [27][28][29][30] . In addition, genistein is effective in ameliorating cardiovascular profiles in experimental models of postmenopausal metabolic syndrome 31 .…”
Section: Evidence From the Women's Healthmentioning
confidence: 99%
“…S. Edgell, University of North Carolina at Chapel Hill. EA.hy 926 cells were generated by fusion of human umbilical vein endothelial cells (HUVEC) with the human lung carcinoma cell line A549 and have been extensively used as a cell model for endothelial function (Fuchs et al 2005). Cells were grown in DMEM medium containing 4.5 g/L glucose and L-glutamine and supplemented with 10% FBS and 1% penicillin/streptomycin (5,000 U/mL).…”
Section: Endothelial Cellsmentioning
confidence: 99%
“…Proteomic studies have even been used to back up claims of the health benefits of soy (Erickson, 2005). In a recent study, an isoflavone from soybean has been found to prevent the regulation of proteins that induce apoptosis, cells which are the prime targets of arteriosclerotic stressors such as oxidised low density lipoproteins (Fuchs et al, 2005).…”
Section: Othermentioning
confidence: 99%